Efficacy of Secukinumab on Moderate-to-severe Plaque Psoriasis Affecting Different Body Regions: a Pooled Analysis of Four Phase 3 Studies. Issue 4 (December 2016) - Menter, Alan; Cather, Jennifer; Jarratt, Michael; Meng, Xiangyi; Guana, Adriana; Nyirady, Judit
Abstract Introduction The impact of psoriasis varies with the body region affected. In addition, patients have different perceptions of disease improvement and treatment satisfaction based on the location of skin clearance with treatment. The monoclonal antibody secukinumab selectively targets interleukin-17A—a central cytokine of psoriasis—and provides rapid and sustained clearance for moderate-to-severe psoriasis affecting all body regions. The objective of this study was to evaluate the efficacy of secukinumab on moderate-to-severe psoriasis affecting the trunk, upper limbs, and lower limbs. Methods Data were pooled from four phase 3 studies. To be included in the analysis for each body region, patients were required to have a Psoriasis Area and Severity Index (PASI) score ≥12 for that body region and psoriasis covering ≥10% of the surface area of that region. Secukinumab was administered at Baseline, Weeks 1, 2 and 3, and then every 4 weeks from Week 4 to 48. Results Across the trunk, upper limbs, and lower limbs, initial PASI subscore responses were sustained to Week 52. At Week 52, trunk (T) PASI 90/100 responses were achieved by 78.4%/71.1% of patients receiving secukinumab 300 mg, respectively, and by 66.3%/56.9% of patients receiving secukinumab 150 mg, respectively. At Week 52, upper limb (UL) PASI 90/100 responses were achieved by 67.3%/59.1% of patients receiving secukinumab 300 mg, respectively, and by 50.3%/43.3% of patients receiving secukinumab 150 mg, respectively. At Week 52, lower limb (LL) PASI 90/100 responses were achieved by 63.9%/55.3% of patients receiving secukinumab 300 mg, respectively, and by 45.1%/36.4% of patients receiving secukinumab 150 mg, respectively. A 50% reduction in mean PASI subscore occurred after 2.8, 2.9, and 3.4 weeks with secukinumab 300 mg on the trunk, upper limbs, and lower limbs, respectively. Conclusion Secukinumab provided robust and sustained efficacy for moderate-to-severe psoriasis affecting the trunk, upper limbs, and lower limbs. Funding Novartis Pharmaceuticals Corporation. Trial registration ClinicalTrials.gov identifiers: NCT01365455, NCT01358578, NCT01555125, and NCT01636687.